N, P and K Content in the EM4 Fermented Made From Mixed Fish Market and Tofu Industry Liquid Wastes to the growth of Azolla microphylla - Hasibuan, Masna; Harahap, Sampe; ', Budijono (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
Liquid wastes originated from fish market and tofu industries are rich in organic materials and it is potencial as basic materials for liquid fertilizer. To understand the N, P and K content in the liquid fertilizer made from fish market and tofu industries liquid waste, a study has been conducted from February to March 2015. The fertilizer was made by fermented the waste with EM4 for 30 days. There were 5 treatments applied, namely 100% market waste (P1); 100% tofu waste (P2); 50% market waste and 50% tofu waste (P3); 75% market waste and 25% tofu waste (P4) and 25% market waste and 75% tofu waste (P5). Result shown that the P4 shown the highest content of N (1,700 mg/L) and P (395.9 mg/L), but the K content in all treatments was almost the same. Addition of the liquid fertilizer into Azolla microphyla media significantly increase the growth of the plant and the best result was also obtained in the plant that was fertilized by P4. Based on data obtained, it can be concluded that the liquid fertilizer made from combination of the market and tofu liquid wastes provided better performance in N and P content.Keyword: Fish market liquid waste, Tofu liquid waste, Liquid Fertilizer, EM4, Azolla microphylla